A Framework Analysis of European Labour Market Policies - Gratiela Georgiana Carica (CES Working Papers, 2011)
The purpose of the paper is to analyse European labour market policies and their integrated guidelines, by highlighting various measures that need to be adopted in order to increase labour productivity, with positive effects on long-term economic development. The paper methodizes the main conditions complied by structural reforms in order to encourage labour employment and the policies that frame a more efficient unemployment insurance system crucial to increase security while encouraging the unemployed to look for a job and to accept a job offer, respectively on flexicurity policies. We found that employment rates are generally associated with large expenses on labour market policies and with an increased number of participants to programs developed within these types of policies. The degree of influence and strong dependence between outcome and labour market policies are illustrated in various ways and discussed within the paper.
Keywords: 330; flexicurity policies; employment protection; unemployment benefits; job search